Andragogika i rozwój kompetencji obywatelskich: formowanie świadomości obywatelskiej specjalistów w kontekście doświadczenia europejskiego. - Oliinyk, Mariia; Volos, Sergii (Edukacja Dorosłych, 2026)
This article provides a comprehensive analysis of the role of andragogy in developing civic competence and consciousness among specialists within the context of European experiences. It argues that andragogical principles–such as self-directed learning, experiential relevance, and learner autonomy – offer a robust framework for integrating democratic values into professional life. The study examines the evolution of EU policy from a narrow vocational focus to holistic lifelong learning strategies that prioritize social inclusion, critical citizenship, and sustainable development. A novel theoretical model of civic-andragogical cycles is proposed to illustrate the dynamic and adaptive nature of civic consciousness. The paper delves into the practical formation of this consciousness, outlining a structured process involving foundational awareness, hands-on application, and reflective evaluation. It identifies key trends across Europe, including community-embedded learning and digital integration, and proposes innovative pedagogical tools like civic impact dashboards and narrative-driven simulations. The study concludes that embedding andragogy in specialist training is crucial for fostering resilient, democratic societies. It recommends reforms that support interdisciplinary collaboration and new metrics for evaluating civic impact, positioning specialists as key agents of social change who contribute to a more cohesive and innovative Europe by bridging professional expertise with community needs.